Fuzzy Integral Sliding Mode Observer-Based Formation Control of Mobile Robots With Kinematic Disturbance and Unknown Leader and Follower Velocities - Boo, Junseok; Chwa, Dongkyoung (IEEE Access, 2022)
Fuzzy integral sliding mode observer (FISMO) based leader-follower formation control with the use of ceiling-mounted camera information is proposed for mobile robots with kinematic disturbance and no information of the velocities of leader and follower robots. Using only the posture information of both the leader and follower robots obtained from the camera sensor, the follower robot is made to follow the trajectory of a target robot that is introduced to render the leader-follower formation control more efficient. As a result, a kinematic tracking error model is proposed in terms of both the posture error between the target and follower robots and the posture error between the origin of the inertial reference frame and follower robot. Because the kinematic disturbance and the velocities of the leader and follower robots are not available, an FISMO is designed to simultaneously estimate the kinematic disturbance as well as the linear and angular velocities of the leader and follower robots. FISMO-based leader-follower output feedback formation control is then proposed based on the estimates of the kinematic disturbance and velocities and the backstepping-like feedback linearization tracking control. The experimental results comparing the proposed FISMO-based method with the robust distance-based tracking control method and integral sliding mode observer (ISMO)-based method are provided to verify the effectiveness of the proposed method.
Keywords: Ceiling-mounted; Ceiling-mounted camera; Formation control; Fuzzy integral; Fuzzy integral sliding mode observer; Integral sliding mode; Kinematic disturbance; Leader-follower; Leader-follower output feedback formation control; Output-feedback; Robot kinematics; Robot vision systems; Sliding-mode observer; Targets tracking; Ceiling-mounted camera; fuzzy integral sliding mode observer; kinematic disturbance; leader-follower output feedback formation control; mobile robots